Studies on Iron(II) and Manganese(II) Complexes with 2´ -Hydroxychalcone - Irudayasamy, M.; Nagarajan, S. (Asian Journal of Chemistry, 2010)
Fe(II) and Mn(II) bis-chelates of the type ML2 where L ═ 2´-hydroxychalcone have been prepared and characterised on the basis of elemental analyses, conductance, magnetic susceptibility, electronic and infrared studies. Both the complexes have been found to be monomeric, low spin and square planar in configuration.